Pilot Study of Effects of Intermittent Pneumatic Compression in the Immediate Peri-Operative Period on Hemodynamic Parameters in Patients After Laparoscopic Gynecologic Surgery - Liu, Yanchang; Tan, Xuhong; Cheng, Yujin; Wang, Baojun; Zhang, Hanyu; Zhang, Lili; Liu, Danyong; Qi, Xiaofei (Frontiers in Surgery, 2022)
The randomized controlled study investigated the impacts of immediate peri-operative Intermittent pneumatic compression (IPC) on hemodynamic indicators in patients undergoing laparoscopic gynecologic surgery. Patients scheduled for elective laparoscopic gynecologic surgery were randomized to control (IPC not used), pre-operative IPC, post-operative IPC, and peri-operative IPC (performed both before and after surgery) groups. Systolic blood pressure (SBP), mean blood pressure (MBP) cardiac output (CO), heart rate (HR) and systemic vascular resistance (SVR) were measured at different time points. The results showed that SBP changes not obviously over time in the control and peri-operative IPC group. Compared with values before surgery, the pre-operative IPC group had a lower SBP (P<0.01) at the end of PACU stay, whereas the post-operative IPC group had a higher SBP (P<0.01) after surgery. All groups exhibited little or no variation in HR, CO and SVR. Conclusion is peri-operative IPC has no major adverse effects on hemodynamic parameters.